USULAN TATA LETAK FRAKTAL UNTUK PABRIK BARU DARI CV PRIMA BANGUN NUSANTARA - Santoso, Santoso; Halim, Chandra (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
CV Prima Bangun Nusantara is a leather manufacturing company which is currently experiencingÂ an increase in demand from consumers and is planning to build a new factory. Since types of productÂ manufactured are varied and tend to fluctuate every 6 months, the layout should be designed flexible toÂ anticipate the changes that may occur. The design begins by counting the number of machines based on theÂ data of production lack provided by the company. The calculation of the number of machines by using aÂ routing sheet is to determine the number of machines suitable for the new factory. After that is creating aÂ relationship among the departments shown in ARD whichis then used to calculate the cost of materialÂ handling (CMH). The calculations show that the value of CMH for âby processâ is Rp.948.505, while theÂ fractal is Rp.905.413. The layout of the fractal generates smaller CMH value by a margin of 5% or as muchÂ as Rp.43.092. To better see the difference in the two layouts, a test is done by changing the data of productÂ types and volume created (in accordance with the conditions of the company, in which the type and volume ofÂ products made may be changed every 6 months). The CMH value for âby processâ layout is Rp.407.283 andÂ for the fractal one is Rp.247.745. The fractal layout generates smaller CMH value with a difference as muchÂ as Rp.159.538 or 39%.